Anti-PCSK9 antibodies for hypercholesterolaemia: overview of clinical data and implications for primary care - Descamps, Olivier S.; März, Winfried (The international journal of clinical practice, 2017)
Objectives To put data from our recent systematic review of phase 3 studies of anti-proprotein convertase subtilisin/kexin type 9 (PCSK9) antibodies into the context of clinical practice. Methods Data from studies previously identified by a systematic review of phase 3 studies of alirocumab and evolocumab and additional references from non-systematic literature searches were used. We evaluated the hypothetical cardiovascular (CV) benefit in cases of typical patients in whom anti-PCSK9 antibodies may be recommended, using preliminary major CV event (CVE) rates from long-term clinical trials of anti-PCSK9 antibodies and from extrapolations derived from correlation between low-density lipoprotein cholesterol (LDL-C) reduction and CV benefit with other lipid-lowering therapies (LLTs). Results Rapid (within 1-2 weeks) and persistent (8-74 weeks) reductions in LDL-C levels were achieved with anti-PCSK9 antibodies. When combined with statins (± ezetimibe), high rates of LDL-C goal achievement were observed (41%-87% with alirocumab and 63%-100% with evolocumab). In long-term alirocumab and evolocumab studies, reductions in major CVEs of 48% and 53%, respectively, were observed. For every 38.7 mg/dL (1 mmol/L) reduction in LDL-C, a 22% reduction in relative CVE risk is predicted. Applying these assumptions to typical patients who have high-very high risk (15%-60% absolute 10-year CVE risk) and elevated LDL-C despite maximally tolerated statins, the 10-year number needed to treat with an anti-PCSK9 antibody to prevent one additional CVE varies from 4 to 26, depending on baseline LDL-C levels and residual absolute CVE risk. Conclusions Anti-PCSK9 antibodies effectively lower LDL-C levels in a broad patient population. While awaiting comprehensive data from CV outcome trials, these agents should be considered in very high risk patients, such as those in secondary prevention and those with familial hypercholesterolaemia who are already receiving maximally tolerated LLTs, have not achieved their LDL-C goal and require substantial reductions in LDL-C.